Stakeholders’ Inquiries About the Systemic Inclusion of Late Adolescent Newcomers to Canada: Moving From Questions to Understandings (LEARNing Landscapes, 2014)
Drawing on data collected during a larger, year-long ethnographic study of a pilot program designed to serve late adolescent newcomers to Canada, this paper uses notions of the phenomenological approach to consider the "inclusion" of late adolescent newcomers in Canada’s education system. The present consideration seeks to frame how some stakeholders implicated in a pilot program to help this particular learner population came to understand the forces that seemingly perpetuated the students’ oppression within the education system. In particular, issues of the parameters of language education, federal and provincial education policies, and funding were identified as the key influences within the phenomenon.
Keywords: inclusion; ethnography; adolescent; learner; education system; language education